Insulin receptor of human cerebral gliomas. Structure and function. - Grunberger, G (1986)
The insulin receptor from human brain tumors of glial origin was examined for the first time using intact cells (from an established cultured human glioblastoma cell line) and partially purified solubilized membranes (from cultured cells and freshly isolated human brain tumors). The structure of the glial insulin receptor subunits was assessed by affinity cross-linking of 125I-insulin with the alpha-subunit of the receptor, neuraminidase treatment of the cross-linked receptor, behavior of the receptor on lectin columns, and electrophoretic mobility of the phosphorylated beta-subunit. The functions of the insulin receptor were examined by measuring specific 125I-insulin binding (receptor concentration, affinity, specificity, pH-, time-, and temperature dependence), insulin-induced down-regulation of the receptor, insulin-stimulated autophosphorylation of the beta-subunit, and phosphorylation of exogenous substrates as well as insulin-stimulated glucose uptake in glioblastoma cells. All of these properties were typical for the insulin receptor from target tissues for insulin action. The insulin receptor of the normal human brain showed the altered electrophoretic mobility and lack of neuraminidase sensitivity of its alpha-subunit previously reported for the rat brain receptor. There was no difference, however, in the functions of the receptor subunits (binding, phosphorylation) from the normal brain tissue and the eight human gliomal tumors. Since the glial elements compose a majority of the brain cells, the "normal" structure and function of their insulin receptor might provide a key to understanding the role of insulin in the carbohydrate metabolism of the human central nervous system.